2002
DOI: 10.1002/ajmg.10601
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of chromosome 13q32 to schizophrenia in a large veterans affairs cooperative study sample

Abstract: Several prior reports have suggested that chromosomal region 13q32 may harbor a schizophrenia susceptibility gene. In an attempt to replicate this finding, we assessed linkage between chromosome 13 markers and schizophrenia in 166 families, each with two or more affected members. The families, assembled from multiple centers by the Department of Veterans Affairs Cooperative Studies Program, included 392 sampled affected subjects and 216 affected sib pairs. By DSM-III-R criteria, 360 subjects (91.8%) had a diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 26 publications
(25 reference statements)
2
19
0
Order By: Relevance
“…It is of interest to note genetic linkage studies involving other psychiatric disorders, most notably schizophrenia and bipolar disorder, have also shown linkage to the 13q region (42)(43)(44)(45)(46)(47)(48)(49)(50). A recent metaanalysis of 11 bipolar disorder and 18 schizophrenia genomic screens showed the strongest evidence for linkage for both disorders to be localized to chromosome 13q (51).…”
Section: Discussionmentioning
confidence: 99%
“…It is of interest to note genetic linkage studies involving other psychiatric disorders, most notably schizophrenia and bipolar disorder, have also shown linkage to the 13q region (42)(43)(44)(45)(46)(47)(48)(49)(50). A recent metaanalysis of 11 bipolar disorder and 18 schizophrenia genomic screens showed the strongest evidence for linkage for both disorders to be localized to chromosome 13q (51).…”
Section: Discussionmentioning
confidence: 99%
“…Brzustowicz et al [1999], in a study of 21 Canadian families, reported a LOD score of 4.42 at marker D13S793. In the 166 schizophrenia families collected by the Veterans Affairs Cooperative Linkage Study of Schizophrenia, Faraone et al [2002] reported a peak LOD score of 1.43 between markers D13S1241 and D13S159. Although there are some negative reports [Coon et al, 1994;Faraone et al, 1998;Kaufmann et al, 1998;Riley et al, 1998;DeLisi et al, 2000;Levinson et al, 2000;Mowry et al, 2000;Schwab et al, 2000;Gurling et al, 2001], it is notable that the peak LOD scores reported by the positive studies cluster in a region ranging from 65 to 95 cM.…”
Section: Results Of Genome Scanmentioning
confidence: 99%
“…Loci have been identified on almost every chromosome, but only a few regions have been replicated across studies. One such region is near the telomere of chromosome 13q (5)(6)(7)(8)(9)(10)(11)(12). Across studies the region of peak linkage is broad, from 13q12 to 13q34.…”
mentioning
confidence: 99%